Impact of Epicatechin Supplementation on Plasma Proteome Profiles in Obese Men and Women—An Exploratory Approach to Sexual Dimorphism - Sousa Filho, Celso Pereira Batista; Ferreira, Allanis Valon; Iwai, Leo Kei; Chaves, Alison Felipe Alencar; Siqueira, Talita Souza; Silva, Victoria; Romualdo, Guilherme Ribeiro [UNESP]; Otton, Rosemari (Wiley, 2025)
PURPOSE: Evidence suggests that consuming epicatechin-rich green tea can increase metabolism in the body, and this metabolic effect might be linked to weight loss in obese subjects. The precise mechanism by which epicatechin influences weight loss is still unclear. Our goal was to identify a specific signature in the plasma proteins of obese individuals, categorized or not by gender (men and women), and to investigate how epicatechin (EC) supplementation affected them. Additionally, we analyzed anthropometric data to assess the potential anti-obesity effects of EC and to identify any gender-related differences that may have emerged. METHODS: In our clinical trial, we provided pure EC (90%) at a daily dosage of 200 mg, administered before the main meal, for three months. The participants were obese men and women with a body mass index (BMI) of 30 kg/m2 or higher. We conducted measurements of body dimensions and performed biochemical blood tests before and after the supplementation with EC, also analyzing the proteome in the plasma samples. FINDINGS: EC supplementation did not alter anthropometric parameters in obese subjects, but it did cause significant molecular changes in their plasma proteome, which varied between men and women. Key proteins like RPL30 were consistently regulated, indicating that EC might activate translational remodeling to adapt to metabolic stress in obesity. CONCLUSIONS: Proteomic profiling reveals early biomarkers of therapeutic efficacy, and future research should examine EC's time-dependent effects on ribosomal biogenesis and metabolic regulation.